Defects‐related early childhood caries as hints of possible maternal–fetal health issues: Evidence from medieval northern Italy. (9th February 2023) - Tesi, Chiara; Ricci, Stefano; Levrini, Luca; Giorgetti, Giovanna; Campagnolo, Monica; Ciliberti, Rosagemma; Fusco, Roberta; Larentis, Omar; Licata, Marta
Abstract: Developmental defects of enamel (DDE) are important markers of stress as they arise from the disruption of ameloblastic activity during enamel matrix secretion and mineralization. Defects on the crowns of the deciduous dentition provide insights into maternal–fetal health because they can emerge during intrauterine development as a result of gestational issues. The presence of previous defective enamel represents one of the most predisposing causes of caries development. Thus, circular caries on the deciduous dentition are considered an indicator of stress because of their ascertained relation with dental enamel defects. In bioarchaeological analysis, these lesions allow us to deepen the question of maternal–fetal health issues in the ancient period. Here, we present evidence of defects‐related early childhood caries in three infants from a medieval cemetery in northern Italy. The findings in the dentitions of the three subjects were investigated with a multi‐analytical approach, including macroscopic examination, microscopic observation, cone‐beam computed tomography (CBCT), scanning electron microscopy (SEM), and histological sections. In the specimens analyzed, the lesions observed in the dentitions appeared to have arisen during the fetal period and then protracted in the postnatal life, suggesting the implication of in utero environment and maternal health in the etiology of defects.